2013
DOI: 10.1590/1414-431x20132694
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial remodeling and bioelectric changes in tachycardia-induced heart failure in dogs

Abstract: In this study, electrical and structural remodeling of ventricles was examined in tachycardia-induced heart failure (HF). We studied two groups of weight-matched adult male mongrel dogs: a sham-operated control group (n=5) and a pacing group (n=5) that underwent ventricular pacing at 230 bpm for 3 weeks. Clinical symptoms of congestive HF were observed in both groups. Their hemodynamic parameters were determined and the severity of the HF was evaluated by M-mode echocardiography. Changes in heart morphology we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
(39 reference statements)
1
0
0
Order By: Relevance
“…Our light microscopic examination of left ventricular myocytes showed disorganized cardiac muscle fibers, cellular necrosis and vacuolar degeneration after 2 weeks of RVP. Furthermore, electron microscopy revealed that significant changes were found in mitochondria, including markedly decreased matrix density, distinct mitochondrial swelling with significant disruption or disappearance of cristae, and vacuolar degeneration, which was in consistent with the study by Song et al…”
Section: Discussionsupporting
confidence: 91%
“…Our light microscopic examination of left ventricular myocytes showed disorganized cardiac muscle fibers, cellular necrosis and vacuolar degeneration after 2 weeks of RVP. Furthermore, electron microscopy revealed that significant changes were found in mitochondria, including markedly decreased matrix density, distinct mitochondrial swelling with significant disruption or disappearance of cristae, and vacuolar degeneration, which was in consistent with the study by Song et al…”
Section: Discussionsupporting
confidence: 91%